Pengaruh Pemberian Youghurt Terhadap Pertumbuhan Gigi Tikus Putih (Rattus Norvegicus Galur Wistar) - Maria Bintang (Indonesian Chemistry Letter, 2001)
The purpose of this research is to get information about the effect of yoghurt on the growing teeth of Rat (Rattus norvegicus strain wistaf). This research used 30 male rats, which divided into three groups. Each group consist of 10 rats. One group was one month old and the others were two and three months old. One of the rats' incisor teeth was cut and the rest length of the teeth were measured by sliding ruler. Each group of the rats was divided into two sub groups. One sub group was given 1,O ml of yoghurt, the others were glven 1,5 mi and 2,O ml of yoghurt once a day for 10 days. The other sub group was given aquadest with the same dose as a control group. Everyday the length of the teeth was measured. The results of this research indicated that yoghurt can accelerate the growth of the rat's teeth, but based on the statistical analyzed it showed nosrgnificant difference.